KAJIAN ETNOSAINS PEMBUATAN TEMPOYAK DALAM TRADISI NYERUIT MASYARAKAT LAMPUNG SEBAGAI SUMBER BELAJAR IPA - Meilani Dwi Lestari; Nur Latifah Amalia Putri; Ni Kadek Dwi Alvina Astuti; Pitrika Daniati Putri; Zahra Vina; Dea Sendianpika; Berti Yolida; Rini Rita T. Marpaung (STKIP Subang, 2026)
The nyeruit tradition is a cultural practice of the Lampung people that utilises tempoyak as an accompaniment to local dishes. This study aims to examine the scientific concepts involved in the production of tempoyak and its potential as a resource for science education based on ethnoscience. The methodology employed was qualitative descriptive research, utilising interviews and a distribution of questionnaires. The results of the study indicate that the tempoyak production process involves fermentation by microorganisms, which causes physical and chemical changes in the durian. These concepts relate to biotechnology, microbiology, and changes in substances within the natural sciences. This study demonstrates that tempoyak production can be utilised as a contextual learning resource whilst introducing the local wisdom of the Lampung community to students.